ESTIMASI VALUE AT RISK DAN EXPECTED SHORTFALL UNTUK HETEROSKEDASTIK RUNTUN WAKTU FINANSIAL DENGAN GENERALIZED PARETO DISTRIBUTION - , HERMANSAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this thesis explain a method for estimating Value at Risk (VaR) and Expected Shortfall of heteroscedastic financial return time series. The method used is combination of GARCH models and Extreme Value Theory (EVT). The GARCH models used to estimate volatility and EVT for estimating the tail of distribution. The distribution used in EVT is Generalized Pareto Distribution (GPD). Furthermore the method used is a method estimation of conditional VaR and conditional Expected Shortfall.